2021
DOI: 10.1007/s00429-021-02315-7
|View full text |Cite
|
Sign up to set email alerts
|

Transmitter and ion channel profiles of neurons in the primate abducens and trochlear nuclei

Abstract: Extraocular motoneurons initiate dynamically different eye movements, including saccades, smooth pursuit and vestibulo-ocular reflexes. These motoneurons subdivide into two main types based on the structure of the neuro-muscular interface: motoneurons of singly-innervated (SIF), and motoneurons of multiply-innervated muscle fibers (MIF). SIF motoneurons are thought to provoke strong and brief/fast muscle contractions, whereas MIF motoneurons initiate prolonged, slow contractions. While relevant for adequate fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 109 publications
3
23
1
Order By: Relevance
“…3c; gray arrows), and may therefore represent the tonic neurons with eye position sensitivity described in squirrel monkey [54]. This assumption would be in line with the recently observed differential histochemical characteristics of MIF and SIF motoneurons [43]. The former population lacks PN and Kv3.1, and expresses reduced Kv1.1, compared to PNpositive SIF motoneurons with strong Kv1.1 and Kv3.1b expression.…”
Section: Markers Of Burst Neurons and Multiple Subpopulations Of Inhi...supporting
confidence: 78%
See 3 more Smart Citations
“…3c; gray arrows), and may therefore represent the tonic neurons with eye position sensitivity described in squirrel monkey [54]. This assumption would be in line with the recently observed differential histochemical characteristics of MIF and SIF motoneurons [43]. The former population lacks PN and Kv3.1, and expresses reduced Kv1.1, compared to PNpositive SIF motoneurons with strong Kv1.1 and Kv3.1b expression.…”
Section: Markers Of Burst Neurons and Multiple Subpopulations Of Inhi...supporting
confidence: 78%
“…Furthermore, via gene-profiling, the authors identified a strong correlation between fast-firing and Kv1.1, Kv3.1 (and Nav1.6) co-expression [37]. This co-expression profile was already observed in the neurons of oculomotor circuitry, such as omnipause neurons (OPNs) [42], pre-oculomotor (dorsal) Y-group neurons [73], and SIF motoneurons within the abducens and trochlear nuclei, as well as the internuclear neurons of the abducens nucleus [43]. Therefore, with the addition of results regarding premotor burst neurons presented in this study, there's significant evidence that the tightly controlled and rapid eye movement types require simultaneous expression of Kv1.1 and Kv3.1 at multiple levels in the oculomotor circuitry.…”
Section: Potassium Channels Perineuronal Nets and Fast-spikingmentioning
confidence: 85%
See 2 more Smart Citations
“…However, a full exploration of frequencies and amplitudes of stimulation is required to further ascertain the differences in the dynamics of MIF and SIF motoneurons. The vestibulo-ocular pathways manifest differential adaptation properties based on their frequency selectivity (Lisberger et al, 1983), thus it is possible that these separate channels (i.e., low vs high frequency) extend to the motoneurons (Dietrich et al, 2017) and that intrinsic membrane properties along vestibular neurons and motoneurons are tuned to determine the firing and discharge properties of MIF and SIF motoneurons (Serafin et al, 1991a,b;Nieto-Gonzalez et al, 2007;Mayadali et al, 2021). Altogether, it can be suggested that individual extraocular motoneurons do not specialize in producing selectively any of the different types of eye movements (see, however, Henn and Cohen, 1972).…”
Section: Discussionmentioning
confidence: 99%